(untitled) (Fiep Bulletin - online, 2015)
Body image is a multidimensional construct that is influenced by the socio-cultural environment, causing dissatisfaction with the body in higher prevalence in female adolescents. This article aims to present the results of a survey of girls in high school students from public schools in the city of Fortaleza, on the internalisation of aesthetic standards culturally imposed. The universe of the research is formed by the 115 students who were in high school in the morning and afternoon shifts, with no need for random sample selection. For data collection was applied SATAQ-3 questionnaire (Sociocultural Attitudes Toward Appearance) taking anthropometric measurements (weight, height) and calculated the body mass index of each student. The participants were divided into groups according to BMI, using the percentiles 15 and 85 for each age group. The points according to the Likert scale were calculated, the means and standard deviations for each group of BMI and for each of the four factors analyzed by SATAQ-3 questionnaire (general internalisation of socially established standards; internalization of the athletic body ideal ; pressure exerted by these standards; media as a source of information on appearance). We found significant results of body dissatisfaction among adolescents, especially in young people about weight, but also in young people with low weight. The distortion of body image in adolescents is configured in a public health problem, affecting students from all body mass indexes, causing the school to become a privileged place for intervention on body image and acquiring healthy habits.